2015
DOI: 10.3758/s13421-015-0555-x
|View full text |Cite
|
Sign up to set email alerts
|

The logic-bias effect: The role of effortful processing in the resolution of belief–logic conflict

Abstract: According to the default interventionist dualprocess account of reasoning, belief-based responses to reasoning tasks are based on Type 1 processes generated by default, which must be inhibited in order to produce an effortful, Type 2 output based on the validity of an argument. However, recent research has indicated that reasoning on the basis of beliefs may not be as fast and automatic as this account claims.In three experiments, we presented participants with a reasoning task that was to be completed while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 48 publications
7
46
0
Order By: Relevance
“…Handley et al (2011) and Howarth, Handley, and Walsh (2016) demonstrated that the same interference occurred in a full between-participants comparison. Participants solved the task in a counterbalanced blocked manner, such that in one block only belief-based responses were required, and in the next block only logic-based responses – and vice versa.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Handley et al (2011) and Howarth, Handley, and Walsh (2016) demonstrated that the same interference occurred in a full between-participants comparison. Participants solved the task in a counterbalanced blocked manner, such that in one block only belief-based responses were required, and in the next block only logic-based responses – and vice versa.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, a question arises with regard to how the model would capture responses under belief instructions. Do we assume that these decisions are based on two distributions of belief-strength, with a logic-based response criterion which shifts according to validity (i.e., a so-called logic-bias, Howarth et al, 2016)? For now, we argue it is safest to rely on the signal detection theory as an excellent measurement model until it is specified in a more dynamic way such that it can also make predictions about the time-course of processing (e.g., Pleskac & Busemeyer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…One possible interpretation of these findings is that the logical inference is available automatically and by default and intervention is required to successfully give a belief judgment. Howarth, Handley, and Walsh (2016) tested this account by examining the impact of a secondary task (Random Number Generation) on both belief-and logic-based judgments while completing both simple (Modus Ponens) and more complex (Disjunctions) reasoning problems. The results replicated earlier findings showing that belief-based judgments produced lower rates of accuracy overall and were influenced to a greater extent than validity judgments by the presence of a conflict between belief and logic for both simple and complex arguments.…”
mentioning
confidence: 99%
“…However, the secondary task, while reducing accuracy of judgments overall, had its greatest impact on logic-based judgments. Howarth et al (2016) interpreted their findings as a conflict between two type-2 processes. They propose that logical responses are available at an early type-1 level, yet require type-2 processing in order to explicitly extract the underlying structure of an argument required for delivering a response based on the validity of the inference.…”
mentioning
confidence: 99%
See 1 more Smart Citation